Pseudomonas aeruginosa USM-AR2/SiO2 biosorbent for the adsorption of methylene blue. Issue 4 (August 2018) - Iqbal, Anwar; Sabar, S.; Mun-Yee, M.K.; Asshifa, M.N. Nur; Yahya, A.R.M.; Adam, Farook
Abstract: A novel biosorbent (RHA-PA) for the adsorption of methylene blue (MB) was developed by immobilizing deactivated Pseudomonas aeruginosa USM-AR2 (PA) cells on mesoporous rice husk ash silica (RHA-SiO2 ). The RHA-SiO2 was synthesized via sol-gel method with fructose as a water-soluble template. The highest Brunauer-Emmett-Teller (BET) surface area (601 m 2 g −1 ) determined from N2 adsorption-desorption analysis was achieved when 20 wt% of fructose was added. The Fourier-transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM) indicate that the PA cells are chemically bonded to the surface of the silica via its surface silanol groups and also deposited in the voids in between the silica particles. Batch biosorption studies were conducted on RHA-PA under different operational parameters (solution pH, initial dye concentrations, contact time and temperature). The biosorption is best described by the Freundlich isotherm and pseudo-second-order kinetic models since it showed better fitting and higher coefficient of determination (R 2 > 0.98 in most of the cases). The maximum biosorption capacities, qmax for MB was 75.7 mg/g, higher than those of other cell biomass reported in the literature. The findings of this study indicate that RHA-PA has the potential as a low-cost and a green biosorbent for the remediation of MB dye.